Neurophysiology and neuroimaging accurately predict poor neurological outcome within 24 hours after cardiac arrest: The ProNeCA prospective multicentre prognostication study. (October 2019) - ; Amantini, Aldo; Carrai, Riccardo; Grippo, Antonello; Lanzo, Giovanni; Lolli, Francesco; Masi, Giulia; Moretti, Marco; Peris, Adriano; Scarpino, Maenia; Spalletti, Maddalena; Bandinelli, Chiara; et al.
Abstract: Aims: To investigate the ability of 30-min electroencephalogram (EEG), short-latency somatosensory evoked potentials (SEPs) and brain computed tomography (CT) to predict poor neurological outcome (persistent vegetative state or death) at 6 months in comatose survivors of cardiac arrest within 24 h from the event. Methods: Prospective multicentre prognostication study in seven hospitals. SEPs were graded according to the presence and amplitude of their cortical responses, EEG patterns were classified according to the American Clinical Neurophysiology Society terminology and brain oedema on brain CT was measured as grey/white matter (GM/WM) density ratio. Sensitivity for poor outcome prediction at 100% specificity was calculated for the three tests individually and in combination. None of the patients underwent withdrawal of life-sustaining treatments before the index event occurred. Results: A total of 346/396 patients were included in the analysis. At 6 months, 223(64%) had poor neurological outcome; of these, 68 were alive in PVS. Bilaterally absent/absent-pathological amplitude cortical SEP patterns, a GM/WM ratio<1.21 on brain CT and isoelectric/burst-suppression EEG patterns predicted poor outcome with 100% specificity and sensitivities of 57.4%, 48.8% and 34.5%, respectively. At least one of these unfavourable patterns was present in 166/223 patients (74.4% sensitivity). Two unfavourable patterns were simultaneously present in 111/223 patients (49.7% sensitivity), and three patterns in 38/223 patients (17% sensitivity). Conclusions: In comatose resuscitated patients, a multimodal approach based on results of SEPs, EEG and brain CT accurately predicts poor neurological outcome at 6 months within the first 24 h after cardiac arrest.